Effect of acute hyperglycemia on intestinal gas transit and tolerance in nondiabetic humans - Harder, Hermann; Hernando-Harder, Ana C.; Franke, Andreas; Krammer, H.; Singer, Manfred V. (Digestion, 2005)
Background: Acute hyperglycemia usually inhibits gastrointestinal motility and hyperinsulinemia may contribute to specific inhibitory effects. However, the influences on postprandial intestinal gas dynamics have not been investigated. Aims: To compare effects of euglycemic hyperinsulinemia and acute fasting hyperglycemia on intestinal gas dynamics in nondiabetics. Methods: On 3 separate days, 10 healthy volunteers were evaluated in randomized order with duodenal glucose, intravenous glucose or saline infusion. Rectal gas evacuation was continuously measured; perception and abdominal girth changes were separately evaluated. After 60 min equilibration, proximal jejunal gas infusion (12 ml/min) was started for 150 min. Results: Acute hyperglycemia failed to cause significant intestinal gas retention (72 ± 64 ml and 53 ± 29 ml final gas retention vs. saline); in contrast, gas clearance was expedited, with a maximal effect between 30 and 105 min (p < 0.001 vs. control). Euglycemic hyperinsulinemia did not significantly influence intestinal gas clearance and no relevant changes of abdominal girth or abdominal and rectal perception were seen, as compared to control (p > 0.05 for all parameters). Conclusion: Accelerated intestinal gas clearance under hyperglycemia is one physiologic factor to avoid postprandial intestinal gas accumulation. Specific underlying mechanisms, which need further investigation, may be disturbed in symptomatic patients.
Gesehen am 09.05.2022